Will the Forests Live Again? - Rao, V. S. (Indian Forester, 1959)
The gradual progress in the attitude towards the conservation of private forests, especially those of the western districts of West Bengal, has been followed up from the date of the enunciation of the first Forest Policy in 1894 to the present day. Hopes for a final settlement of the issue favourable to the prosperity of the tract run side by side with misgivings. Verily may it be said of the present: "Never have so many been so much at the mercy of so few".